Parameter optimization of fused deposition modeling process for 3D printed prosthetic socket using PCR-TOPSIS method - Abd. Latif, Mohd Juzaila; Alkahari, Mohd Rizal; Yob, Mohd Shukri; Lim, Gordon Tze Yih; Musa @ Othman, Masjuri; Abdul Rahman, Mohd Nazim; P. Rajaandra; Nguyen, H. Q. (Universiti Malaysia Perlis, 2022)
Prosthetic socket plays the most important role in lower limb prosthesis. The conventional fabrication process of prosthetic socket is labor intensive and time-consuming. The application of additive manufacturing technology may greatly simplify the process. One of the main concerns on the reliability of 3D printed prosthetic socket is its structural strength due to the various 3D printing parameters that may influence the strength of 3D printed products. Furthermore, most of the previous studies focused on single parameter and the effect on socket strength. Thus, this study aimed to examine the optimization of fused deposition modeling printing parameter of 3D printed prosthetic socket in term of strength, fabrication time and weight. Three FDM printing parameters were studied which included layer height, nozzle diameter and infill percentage. The data was analyzed using Taguchi and PCR-TOPSIS methods. Based on the result, it was concluded that the most effective combination of printing parameter is 1.0 mm nozzle diameter, 0.48 mm layer height and 30% infill percentage. In addition, infill percentage shown the highest influence towards the responsive values followed by layer height and nozzle diameter.